Ecosystem carbon stock variation along forest stand ages: insight from eastern coast mangrove ecosystem of India - Muktipada Panda; Bikash R. Dash; Sudam C. Sahu (Ecological Processes)
Abstract Background The mangrove ecosystem has the highest carbon sink potential which significantly contributes to bringing carbon neutrality. Understanding the carbon stock dynamics along the age of forest stands in the mangrove forest ecosystem is of significance for managing the forests and their carbon accumulation. This study aimed to estimate the forest structural attributes, biomass and total ecosystem carbon stock (TECS) of old natural (age > 50 years) and young planted (age ~ 20 years) mangrove forest stands at Bichitrapur Mangrove Reserve Forest in eastern coast of India. We also attempted to understand the interrelationship of structural attributes, biomass and soil properties in the mangrove forests. To achieve the results, twenty random plots were established (size: 20 m × 25 m) and suitable allometric equations along with species-specific wood density values were used to estimate the biomass and carbon stock. Results Altogether, 29 plant species (18 exclusive and 11 associate species) were recorded. The mean total biomass (± SE) and soil organic carbon (at 30 cm depth) were 165.31 ± 20.89 t ha−1 and 40.20 ± 1.24 t C ha−1 for young stands, and 586.12 ± 56.74 t ha−1 and 49.68 ± 2.39 t C ha−1 for old stands, respectively. Among mangrove species, Avicennia marina contributed the highest vegetation biomass in both forest stands (59.72 t ha−1 and 262.28 t ha−1 in young and old stands, respectively), followed by Avicennia officinalis (35.05 t ha−1) and Sonneratia apetala (26.09 t ha−1) in young stand and Avicennia alba (169.28 t ha−1) and Avicennia officinalis (115.58 t ha−1) in old stand. The mean TECS was 235.62 ± 27.34 t C ha−1. The contribution of vegetation and soil to TECS was 63% and 37% in the young stand, whereas in the old stand it was 83% and 17%, respectively. The correlation analyses revealed that mean stand height (r = 0.87), basal area (r = 0.99), soil nitrogen (r = 0.76), potassium (r = 0.78), and carbon (r = 0.80) were significantly positively correlated with total biomass at p < 0.01. Conclusions Our results demonstrate that old mangrove forest stands store substantially high carbon stock than young planted forest stands, implying the role of forest age in determining the carbon storage potential of mangrove ecosystems.